Perceived Physical Activity Levels and Objective Measures: A Mixed-Methods Study of Residents Aged 65 and Above in Assisted Living Homes in Australia - Samaher Alowaydhah; Ishanka Weerasekara; Sarah Walmsley; Sally Keir; Jodie Marquez (Journal of Aging Research)
Conclusion: This study provides valuable insight into the demographic and health factors contributing to higher levels of activity, and the perceptions of activity among older adults vulnerable to health conditions associated with inactivity.